Research of Factors Which Influence the Investment Activity of the Companies - ЧеркасоваВиктория Артуровна; ТепловаОльга Юрьевна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2011)
Authors: Victoria A. Cherkasova National Research University The Higher School of Economics vcherkasova@hse.ru Olga I. Teplova In the article are considered various approaches to the problem of the choice of investments’ level of the company: a number of the factors which influence the investment activity of the company is revealed; influence of return on investments (ROI) on the investment policy is analysed. The review of economic researches on determinants of investment policy of the companies is studied, various approaches to calculation of ROI are considered. The basic steps and results of the empirical research based on the russian companies’ data are presented.